Sarcopenia in IBD patients and the role of nutritional and physical activity interventions in its management – a systematic review - Jurkiewicz, Michalina; Siembab, Karolina; Białeta, Julia; Rowińska, Katarzyna; Napieralska, Agnieszka; Garbarczyk, Wiktor; Kapla, Albert; Černohorská, Alicja; Bednarczyk, Daria; Pysiewicz, Wiktoria (Quality in Sport, 2025)
Inflammatory Bowel Diseases (IBD), namely Ulcerative Colitis and Crohn’s Disease, are chronic, relapsing, inflammatory conditions of the gastrointestinal tract, with multifactorial pathophysiology. They are often complicated by sarcopenia, which is defined as a condition of skeletal muscle system characterized by a generalized loss of skeletal muscle mass and muscle function. Sarcopenia and pre-sarcopenic conditions are important to be diagnosed and maintained in the course of IBD, as they exert detrimental impact on the therapy outcomes. There is increased probability of therapy failure such as change of pharmacotherapy, hospitalization or surgical intervention, in individuals with sarcopenia. There are multiple mechanisms underlying this complication in IBD: e.g. malnutrition, disrupted gut microbiota, pharmacotherapy, and elevated inflammatory cytokines. Nevertheless, there are some possible interventions that can be undertaken to counteract this complication. Fundamental interventions in IBD-related sarcopenia are: accurate nutrition, micronutrient supplementation and properly adjusted physical activity. IBD patients should do 3-5 moderate-intensity trainings per week. Exercise programs should combine aerobic, resistance and flexibility exercises. Resistance training is the first-line therapy in management of sarcopenia. This kind of exercises was proven to improve muscle mass, strength and physical performance. Aerobic activity is also important as it enhances metabolic capacity of the muscles. However, further research is required to define specific recommendations for nutritional and exercise interventions validated for the group of patients with IBD-related sarcopenia.